Planetário: espaço não formal para o ensino de ciências - Santos, Isabela Marcelina de Oliveira (2019)
The Planetarium is a non-formal teaching space with great pedagogical potential to promote the popularization of several areas of knowledge such as: Astronomy, Physics, Chemistry, Biology, Mathematics, History and Geography. The general objective of this work is to elaborate and present interdisciplinary proposals of Basic Education for dome sessions in the Planetarium and for this the research methodology was divided in four stages: bibliographic research; exploratory research; preparation and application of presentations; and analysis and discussion of the results. Thus, it was clear that researchers in the area of science education are interested in non-formal education, especially at museums, science centers and planetariums. The diversity of the videos used in the dome sessions is enchanting, both in the themes and in the target audience. The generated educational product is a scriptbook for planetarium sessions using the Stellarium app and original videos. The book contains scripts for Planetarium sessions based on research done, existing videos and the choice of themes.